The Study of Correlation Between Heavy Metal Levels in Environment and Autism Case in Samarinda and Bantul - Hasim; Andi Sofyan Hasdam; Ahmad Sulaeman; Moh. Hasan Machfoed (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Autism is a disorder of pervasive development in children, which until now,the exact cause is unknown. The strongest allegations are genetic andenvironmental factors, especially heavy metals. This study aims to look therelationship between the occurrence of heavy metals pollution with theautism cases in Samarinda and Bantul. This study was carried out bymeasuring the levels of heavy metals in fish, vegetables, water and soil andalso hair of 30 autistic children and 10 control children in Samarinda and 30autism 4 control in Bantul.All samples were measured their heavy metalcontent (As, Hg, Cd, Pb) at The Central Nuclear Applied Science andTechnology Laboratory in Bandung. The result compares with the standardvalue and were found that the samples was exceeding the heavy metals valuein Samarinda is Arsenic in fish, lead in fish. While in Bantul, Mercury in fish,mercury in vegetable and lead in vegetable. In the hair samples result, thelevel of arsenic, mercury and lead were higher in autism children comparedto controls in Samarinda, while in Bantul only mercury and lead levels arehigher in hair of autism children than controls. Cadmium levelswere nodifference between autistic and control hair both in Samarinda and Bantul.